The impact of the prostaglandin D2 receptor 2 and its downstream effects on the pathophysiology of asthma. Issue 4 (20th August 2019) - Brightling, Christopher E.; Brusselle, Guy; Altman, Pablo
Abstract: Current research suggests that the prostaglandin D2 (PGD2 ) receptor 2 (DP2 ) is a principal regulator in the pathophysiology of asthma, because it stimulates and amplifies the inflammatory response in this condition. The DP2 receptor can be activated by both allergic and nonallergic stimuli, leading to several pro‐inflammatory events, including eosinophil activation and migration, release of the type 2 cytokines interleukin (IL)‐4, IL‐5 and IL‐13 from T helper 2 (Th2) cells and innate lymphoid cells type 2 (ILCs), and increased airway smooth muscle mass via recruitment of mesenchymal progenitors to the airway smooth muscle bundle. Activation of the DP2 receptor pathway has potential downstream effects on asthma pathophysiology, including on airway epithelial cells, mucus hypersecretion, and airway remodelling, and consequently might impact asthma symptoms and exacerbations. Given the broad distribution of DP2 receptors on immune and structural cells involved in asthma, this receptor is being explored as a novel therapeutic target.